DESIGN AND RESEARCH OF INTELLIGENT CONTROL SYSTEM FOR BELT CONVEYOR - WANG JiDong; SUN JianYan; HU MeiLing (Jixie qiangdu)
According to the working process and fault characteristics of belt conveyor, a safe and reliable intelligent control system solution is proposed. The solution consists of centralized control system and field control system. It adopts the control mode of PLC and host computer. PLC is used to collect and control the data of the equipment in the whole belt conveyor. The intelligent control of belt conveyor is realized by issuing control commands to the system equipment through the interface of the upper computer and displaying the operation status and fault alarm information of each equipment intuitively and dynamically. The main technical points of the system are introduced from the aspects of overall solution, hardware selection, software design and control flow.